PEMBINAAN NILAI-NILAI KEPEMIMPINAN PADA ANAK USIA DINI MELALUI PENDIDIKAN AGAMA HINDU (Educemara: Jurnal Pengabdian Masyarakat, 2024)
Education is actually oriented towards life skills and competencies that produce valuable products. So, learning is expected to provide an integrative competency experience. Students' skills and instilling leadership values need to be developed and instilled from an early age. Direct and indirect learning can be obtained from observing, asking questions, gathering information, communicating and educational games. This is what encourages the implementation of community service which emphasizes leadership values in early childhood through Hindu Religious Education using game and story teaching methods. So that the implementation is fun and not boring for students, especially children at an early age.
Keywords: Leadership Values, Early Childhood, Hindu Religious Education